A Comprehensive Study of the Carbon Contamination in Tellurite Glasses and Glass‐Ceramics Sintered by Spark Plasma Sintering (SPS). Issue 1 (6th December 2013) - Bertrand, Anthony; Carreaud, Julie; Delaizir, Gaëlle; Duclère, Jean‐René; Colas, Maggy; Cornette, Julie; Vandenhende, Marion; Couderc, Vincent; Thomas, Philippe; Ballato, J.
<x xml:space="preserve">Abstract</x> Highly transparent tellurite glasses and glass‐ceramics based on the 85TeO2–15WO3 composition (mol%) were produced by spark plasma sintering (SPS) from powders previously prepared by the conventional melt‐quenching technique and then grinded. We report a study based on the understanding of carbon contamination that is commonly observed by this nonconventional sintering technique and which constitutes a drawback for optical applications. First, the influence of the particle size of the initial amorphous powders as well as an additional pressureless sintering step prior to SPS experiments and the use of a physical carbon diffusion barrier have been investigated to reduce the carbon contamination in glass bulks. Second, once reducing the carbon contamination, glass‐ceramics were obtained by varying the SPS conditions. The noncentrosymmetric γ‐TeO2 phase crystallized within the bulk volume while maintaining good optical transparency and led to the generation of second harmonic. This approach paves the way to further applications in the domain of linear and nonlinear optics.